TO A QUESTION OF THE ANALYSIS OF STABILITY OF COMPLICATED HYDRODYNAMIC SYSTEMS THAT ARE UNDER MAN-CAUSED PRESS CONDITIONS (ON AN EXAMPLE OF LUGANSK CITY) - KOSHLIAKOV, O.; MOKIIENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this paper was given the rating results of stability for studying complicated hydrodynamic systems that are under man-caused press conditions. For this purpose was used the constantly working hydrogeological model of Lugansk city territory and it was created the statistical models of hydrodynamic pressure distribution. It allowed recommend the rational construction of underground water monitoring system under conditions of action of the natural and anthropogenous factors that influence the regime of water intake wells operation.